Design of an adaptive output feedback controller for LTI systems with sinusoidal disturbances - Yılmaz, Cemal Tuğrul. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2017., 2018)
This thesis is a theoretical study which develops an adaptive output feedback controller for LTI system driven by unknown sinusoidal disturbances. Two speciﬁc systems are considered. As the ﬁrst one is the unknown minimum-phase LTI system with known relative degree and system order, the second one is the known LTI system with the presence of a known input/output delay. The controller objective for both systems is to reject the disturbances and make the equilibrium of the closed loop system stable. In the ﬁrst problem, the controller design procedure is based on K-ﬁlter tech nique, disturbance parametrization, and adaptive backstepping. It is proven that the equilibrium at the origin is globally uniformly stable and the output signal tracks a given reference signal asymptotically. For an additive unmodelled noise, the robust ness of the closed loop system is also discussed. In the second problem, the essence of the control design is composed of disturbance parametrization, state and distur bance observer design. The controller compensates the delays, rejects the disturbances and achieves the exponential stability of the equilibrium of the closed-loop system by estimating the disturbance and state perfectly.
Keywords: Automatic gain control.